2023
DOI: 10.1039/d2qi02161g
|View full text |Cite
|
Sign up to set email alerts
|

Distinct insight into the use of difunctional double-decker silsesquioxanes as building blocks for alternating A–B type macromolecular frameworks

Abstract: A distinct look at known, hydrosilylation reactions used for the formation of DDSQ-based linear A–B alternating macromolecular systems with DPn > 1000 is presented. Selected physicochemical properties of obtained hybrid co-polymers were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…Also, it was reported that the presence of electron-withdrawing atom(s) increases the reactivity of Si–H moiety. 51 This is in accordance with the Chalk–Harrod's mechanism. 47,63…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Also, it was reported that the presence of electron-withdrawing atom(s) increases the reactivity of Si–H moiety. 51 This is in accordance with the Chalk–Harrod's mechanism. 47,63…”
Section: Resultssupporting
confidence: 82%
“…Also, it was reported that the presence of electron-withdrawing atom(s) increases the reactivity of Si-H moiety. 51 This is in accordance with the Chalk-Harrod's mechanism. 47,63 The obtained results facilitated the selection of the optimal location of the Si-H and Si-Vi bonds in applied reactants.…”
Section: Synthesis Of the First Generation Of Carbosilane Dendrimers ...supporting
confidence: 82%
See 1 more Smart Citation
“…To obtain these polymers, reactive sites for polycondensation and polyaddition should be introduced; e.g. , amino, 8 vinyl, 4 b – d hydrosilyl, 9 and epoxide 4 a groups. Incompletely condensed POSS (IC-POSS), which is characterized by its partially open cage structure, is instrumental in introducing reactive sites to derive bifunctional monomers (Fig.…”
Section: Introductionmentioning
confidence: 99%